Multi-objective Optimization Design of Gear Pump with High Trapped-oil Performance - Sun Fuchun; Li Yulong; Yuan Ying; Wen Changming; Zhong Fei (Jixie chuandong)
The optimization design for solving trapped-oil pressure relief of gear pump under higher speed is studied,taking the modulus,tooth number and modification coefficient as optimization variable,by the analysis of the maximum trapped-oil volume and maximum relief area,the two objective functions of are established releasing the trapped-oil pressure. Combining with the current requirements of the flow pulsation rate and the pump volume per unit rated flow and the radial force corresponding of external gear pump,the optimization model is built by using the SUMT technology that full name is sequential unconstrained minimization technique.Aiming at the result before optimization and after,the simulation analysis and verification of trapped oil pressures are respectively carried out. The results indicate that,the larger the modulus is and the smaller the tooth number and the modification coefficient are,the larger the maximum relief area is and the better the relief effect of trapped-oil pressure is. The smaller the tooth number and the modification coefficient are,the larger the maximum trapped-oil flow is and the worse the relief effect of trapped-oil pressure is,so an optimization problem is existed. The simulation result of an example is consistent with the experimental results provided by the literature before the optimization design,and the error between the experimental results and the simulation results is controlled in near 4. 9%,the reliability of the trapped-oil model is validated. After the optimization design,the value of the maximum trapped-oil pressure is reduced by 65. 41%,the relief effect of trapped-oil pressure is obvious.